Diagnóstico de la contaminación acústica generada por el parque automotor en el perímetro urbano de la ciudad de Piñas, provincia de El Oro - Galarza Murillo, Jahaira Lisbeth (2023)
The following investigation was carried out to know the sound pressure levels generated by the automotive fleet in the urban perimeter of the city of Piñas, province of El Oro; An area of 48.16 hectares was sampled where 339 points were measured at three times (07:00 - 09:00, 11:00 - 13:00 and 17:00 - 19:00) with a duration of 30 minutes in 3 repetitions of 10 minutes, for which an approved integrated sound level meter was used, in turn the number of heavy and light vehicles, motorcycles, electric cars and bicycles was counted. In the measurements of the sound pressure levels, a minimum value of 66.6 dB was obtained in the urban perimeter, that is to say that all the measurements carried out exceed the maximum permissible limits established by the TULSMA. In the statistical analyzes carried out for the vehicular categorization, it should be mentioned that the greatest presence of heavy and light vehicles is found on Av. Ángel Salvador Ochoa, while Av. Independencia and Eloy Alfaro Street present the highest registrations of motorcycles. Subsequently, noise maps were generated using the Geographic Information System, ArcGIS software, with the IDW interpolation tool, using intervals and color coding to recognize the areas with the lowest or highest decibels recorded in the measurements. Finally, prevention, mitigation, and training strategies were proposed for the reduction of sound pressure levels using, through a FODA matrix, developed in two workshops with focus groups. Keywords: Sound pressure, noise maps, urban perimeter, vehicles.